Left Ventricular Dysfunction Switches Mesenchymal Stromal Cells Toward an Inflammatory Phenotype and Impairs Their Reparative Properties Via Toll-Like Receptor-4. Issue 23 (6th June 2017) - Naftali-Shani, Nili; Levin-Kotler, La-Paz; Palevski, Dahlia; Amit, Uri; Kain, David; Landa, Natalie; Hochhauser, Edith; Leor, Jonathan
Abstract : Background: Little is known about the potentially unfavorable effects of mesenchymal stromal cell (MSC) activation on the heart. MSCs can respond to tissue injury by anti- or proinflammatory activation. We aimed to study the potential negative interaction between left ventricular dysfunction (LVD) and MSC activation. Methods: We isolated MSCs from cardiac and subcutaneous fat tissues of mice with LVD 28 days after myocardial infarction or sham operation. To evaluate the effect of LVD on MSCs, we characterized cardiac MSCs and subcutaneous MSCs in vitro. Subsequently, we injected MSCs or saline into the infarcted myocardium of mice and evaluated LV remodeling and function 28 days after myocardial infarction. To test the hypothesis that toll-like receptor 4 ( TLR4 ) mediates proinflammatory polarization of MSCs, we characterized cardiac MSCs from TLR4 -/- and wild-type (WT) mice after inflammatory stimulation in vitro. Next, we transplanted cardiac MSCs from TLR4 -/- and WT male mice into the infarcted myocardium of female WT mice and evaluated infarct size, MSC retention, inflammation, remodeling, and function after 7 days. Results: LVD switched cardiac MSCs toward an inflammatory phenotype, with increased secretion of inflammatory cytokines as well as chemokines. The effect of LVD on subcutaneous MSCs was less remarkable. Although transplantation of cardiac MSCs and subcutaneous MSCs from LVD and sham hearts did not improve LV remodeling and function, cardiac MSCs from LVD exacerbated anterior wall thinning 28 days after myocardial infarction. The inflammatory polarization of cardiac MSCs by LVD was mediated by TLR4, as we found less secretion of inflammatory cytokines and higher secretion of anti-inflammatory cytokines from activated cardiac MSCs of TLR4 -deficient mice, compared with WT cardiac MSCs. Significantly, TLR4 deficiency preserved the expression of CD47 (don't eat me signal) on cardiac MSCs after both TLR4 stimulation in vitro and transplantation into the infarcted heart. Compared with WT cardiac MSCs and saline, TLR4 -/- cardiac MSCs survived in the cardiac tissue and maintained their reparative properties, reduced infarct size, increased scar thickness, and attenuated LV dilatation 7 days after myocardial infarction. Conclusions: The environment of the failing and infarcted myocardium drives resident and transplanted MSCs toward a proinflammatory phenotype and restricts their survival and reparative effects in a mechanism mediated by TLR4 . Abstract : Supplemental Digital Content is available in the text.